Enhancing fiber recovery from wastewater may require toilet paper redesign. (10th July 2020) - Li, Simeng; Wu, Zhuangzhuang; Wu, Zixin; Liu, Guoqiang
Abstract: Each day a large amount of toilet paper (TP) is flushed into sewers. Recovering the disintegrated fibers from wastewater can reduce the treatment cost and the recovered fibers have some value-added applications. However, typical preliminary treatment units are inefficient at capturing these small-sized fibers. Although sieving can recover them effectively, it is rarely used due to high costs. Results from this study suggested that redesigning TP to disintegrate less in water can be a more cost-effective approach. Here, we evaluated the disintegration of TP in sewers and fiber recovery through screening, sieving, and sedimentation. We found that the highly disintegrated TP are significantly more challenging to retrieve using conventional approaches. Fine screens with an opening size of 3 mm recovered only 45.7% of the TP fibers. Sieves with 0.1–1 mm openings retrieved up to 94.5% of the TP fibers but were very prone to clogging. Further, the fiber recovery by preliminary treatment was heavily impacted by the TP disintegration degree, which was found to be predominantly affected by the flow motion, wetting time, and inherent stability of TP. A life-cycle cost (LCC) analysis showed that redesigning TP (i.e., designing it to disintegrate into fragments rather than separated fibers) could significantly promote fiber recovery with the existing infrastructures. The 15-y operational costs could be reduced by up to 46% by using redesigned TP. This work presents a promising way to facilitate TP fiber recovery from wastewater at lower cost; pilot and full-scale surveys must be conducted to evaluate feasibility. Graphical abstract: Image 1 Highlights: TP disintegration results in fibers that are difficult to retrieve from wastewater. Fine screens recovered 45.7% of TP fibers. Sieves retrieved up to 94.5%, but can be clogged easily. Lowering TP disintegration by 10–50% may reduce water treatment costs by 12.1–18.6%. Breakup of TP into 0.5–1.0 cm fragments may reduce water treatment costs by 46%.